Pharmacare 2023: enhancing pharmacist-in-training’s skills / Farhana Fakhira Ismail - Ismail, Farhana Fakhira (Faculty of Pharmacy, 2024)
Pharmacare 2023 constituted a pivotal component of the PHC670 curriculum, specifically within the framework of Community Pharmacy. This assessment which involved final-year students from Faculty of Pharmacy, Universiti Teknologi MARA, Puncak Alam aimed to cultivate adept communication skills for disseminating health-related information to the public. Apart from local students, this event involved 6 students from Universiti of Pakuan, Indonesia.